Pluralisme dan multikulturalisme: Pembentukan masyarakat madani - Rizky, M. Alfan (Maliki Interdisciplinary Journal, 2026)
Indonesia is known as a pluralistic society in terms of ethnicity, language, customs, and religion. Therefore, pluralism and multiculturalism can create an understanding that every individual feels valued and has a responsibility to live together in their community. A reality that cannot be ignored is the existence of diversity that arises from ethnicity, culture, language, and religion that is often forced into an incompatible understanding, between minority and majority groups, as well as differences in economic and social strata that can give rise to differences of opinion as a problem that has the potential to become a conflict. Therefore, for pluralism and multiculturalism in Indonesia to run effectively, Indonesian society needs to develop the values of multiculturalism in ethnicity, religion, language, and culture. By implementing pluralism and multiculturalism, Indonesian society in the future will become a civilized society